Amelioration of the “Truskavetska” bottled water by hydrogen-riching - Savytskyi, Ivan; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2025)
Background and aim. The “Truskavetska” bottled water (TW) is officially classified as table water and is not considered medicinal. Recently, it rats experiment we found that enrichment of TW with Hydrogen generally has a favorable effect on its stress-limiting capacity, associated with antioxidant activity. We hypothesized that enrichment of TW with Hydrogen may increase its physiological/therapeutical activity, in particular in relation to patients with chronic pyelonephritis. Testing this hypothesis was the aim of this study. Material and methods. The object of observation were 22 men with chronic pyelonephritis. We determined the leukocyturia and bacteriuria levels and recorded EEG, HRV, phagocytosis, lipids peroxidation as well as routine hematological and biochemical blood parameters. The survey was conducted twice: on admission and after week of drinking of Naftussya bioactive water (NW) or TW by 200 mL for 1 hour before meals three times a day, or TW by 100 mL, mixed before use with 100 mL of regular water, but enriched with Hydrogen. Results. It was found that TW does not affect catalase activity and blood levels of α2-globulines and sialic acids, while NW significantly increases them; after enrichment of TW with Hydrogen, it partially acquires the properties of NW, although it is still significantly inferior to it. On the other hand, Hydrogen gives TW the ability to reduce blood levels of MDA, bilirubin, prothrombin and eosinophils, which also brings it closer to NW. Instead, hydrogen-enriched TW even slightly outperforms NW in terms of enhancing the intensity of blood neutrophils phagocytosis, increasing serum lysozyme activity and urinary amylase excretion, on the one hand, and reducing leukocyturia and bacteriuria, blood levels of CIC and HDLP cholesterol, as well as vagal tone, on the other hand. In addition, enrichment of TW with Hydrogen eliminates caused by it the decrease in the blood content of erythrocytes and hemoglobin and even reverses the decrease in the entropy of EEG and HRV as well as PSD of theta-rhythm in occipital loci. Conclusion. Enriching the low-activity "Truskavetska" bottled water with Hydrogen significantly increases its physiological activity to a level comparable to those of therapeutic Naftussya water, which is manifested in a favorable effect on leukocyturia and bacteriuria as well as phagocytosis, metabolism, and erythron in patients with chronic pyelonephritis.